Prebiotic Iron Originates the Peptidyl Transfer Origin. (19th February 2019) - Lin, Shin-Yi; Wang, Ying-Chi; Hsiao, Chiaolong
Abstract: The ribosome is responsible for protein synthesis in all living organisms. It is best known to exist around 3.5–3.7 Ga whereat life on Earth inhabited anoxic environment with abundant soluble irons. The RNAs and proteins are the two biopolymers that constitute the ribosome. However, both proteins and RNAs require metal cations to fold and to function. There are four Mg-microcluster (Mg 2+ -μc) structures conserved in core of large subunit, and the 23S ribosomal RNA (rRNA) was shown to catalyze electron transfer in an anoxic environment in the presence of Fe 2+ . The Mg 2+ -μc features two idiosyncratic Mg 2+ ions that are chelated and bridged by a common phosphate group and along with that, the adjacent residues of RNA backbone together forming ten-membered chelation ring(s). Here, we utilized four rRNA fragments of the large subunit 23S rRNA of Haloarcula marismortui, that includes the residues that form the four Mg 2+ -μc's. These four rRNA fragments are shown competent to assemble with Mg 2+ . Our results show that when these rRNA fragments fold or assembly in the presence of Fe 2+ under anoxic conditions, each Fe 2+ -microcluster can catalyze electron transfer. We propose that Fe 2+ -microclusters of the ribosome, which use Fe 2+ as a cofactor to regulate electron transfer, are pivotal and primordial and may be an origin in evolution of the ribosome.